The liquid modernity of Bauman and its implications in a proposal for citizenship education (Praxis Educativa, 2025)
This article is developed based on a theoretical and bibliographical research of an analytical nature that aims to answer the following question: How can the conception of liquid modernity of Bauman be a challenge to the proposal of education for citizenship? The text is structured in two parts: in the first, we discuss the concept of liquid modernity of Bauman. In the second, the current challenges for promoting education for citizenship in the context of liquid modernity. Finally, we point out some possible paths for the promotion of education for citizenship in an educational scenario guided by the principles of liquid-modern life.Keywords: Liquid Modernity. Education. Citizenship.